An look at gender diverse community participation in the social environment (Dissertare, 2022)
The gender diverse community is characterized by showing different orientations and sexual identities in the human species. It includes a multiplicity of lives in society and a variety of emotional, gender and sexual orientations, expressions and identities, such as: lesbian, gay, bisexual, trans and intersex. The social participation of these people is still not accepted in many societies, due to complex situations such as homophobia, lesbophobia, biphobia and transphobia; that favor violence against these people. The fundamental objective of this article is to analyze the participation of the gender diverse community in the social sphere. It has a qualitative approach, documentary design, supported by bibliographic review and content analysis. As conclusions, it is highlighted that, despite the struggles and movements of social protest, gender diverse communities still face difficulties in accessing formal jobs, and are victims of discriminatory behavior in educational contexts; therefore, social, political and cultural actions must be promoted for the real recognition of this group. It is essential to include the approach to gender diversity in the curricula of school educational institutions, which means reinforcing sexual education, including diversity in order to eradicate discriminatory behaviors and promote the meeting of knowledge on diverse family models.
Keywords: gender diversity; participation; dissident sexuality; human rights